Electrical & electronic circuits for engineers & technicians : volume 2 - Latorilla, Elpidio (Mandaluyong City, Philippines : National Book Store, 2005)
This collection is the second volume in the series. It contains 101 practical circuits grouped in ten general applications. This is one proof of the circuits versatility. You can combine several circuits into one large module to create a powerful electronic device specially designed for your exclusive projects.
Audio and music -- Hobby and shop -- House and car -- Radio frequency -- Hobby and games -- Power supplies and charger -- Tester & meters -- Digital and computers -- Oscillators and counter -- Auxiliary .
Includes index.
Keywords: ELECTRICAL CIRCUITS